The Importance Of Whistleblower Protection In The Environmental Sector - Riza Amalia; FX Sumarja; Muhammad Akib; Ria Wierma Putri (PT. Padang Tekno Corp, 2024)
Whistleblower protection in the context of the environmental and Natural Resources sector is a key element in efforts to prevent corruption and sustainable management. This sector has a direct impact on human lives and societal well-being, and therefore, maintaining its integrity is essential. This research outlines the importance of whistleblower protection in the environmental and natural resources sectors. The method used in this research is normative with a doctrinal approach. Protection of whistleblowers has an important role in maintaining transparency and accountability in the environmental and natural resources sectors. Through the protection provided to whistleblowers, corrupt practices can be exposed and accountability can be realized. However, challenges and limitations still exist, and concerted efforts are needed to improve the implementation and effectiveness of these laws. With continued efforts, whistleblower protection laws can become a powerful tool in promoting transparency and accountability in the environmental and natural resources sectors.